2013
DOI: 10.1007/s11908-013-0364-y
|View full text |Cite
|
Sign up to set email alerts
|

Does the Nose Know? An Update on MRSA Decolonization Strategies

Abstract: Colonization with methicillin-resistant Staphylococcus aureus (MRSA) is an important step in the pathogenesis of active infection and is a key factor in the epidemiology of MRSA infection. Decolonization of patients found to have MRSA carriage may be of value in certain patient populations, especially those undergoing elective surgery. However, the most commonly used agent for decolonization, mupirocin, comes with a considerable risk of resistance if widely employed. Recent studies of other novel agents for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 74 publications
2
39
0
1
Order By: Relevance
“…Interestingly, our findings indicated that the synbiotics treatment effectively suppressed an increase in the detection rate of C. difficile after surgery. Therefore, the value of synbiotics should be considered from the point of view of not only SSI prevention in individual patients but also the inhibition of multidrug-resistant bacteria [52] or antibiotics-related infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our findings indicated that the synbiotics treatment effectively suppressed an increase in the detection rate of C. difficile after surgery. Therefore, the value of synbiotics should be considered from the point of view of not only SSI prevention in individual patients but also the inhibition of multidrug-resistant bacteria [52] or antibiotics-related infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Other interesting investigational decolonizing agents that need more study include bacteriophages, fecal microbiota transplant, and probiotics (76,148). Clinical trials should be performed to investigate these agents.…”
Section: Selective Digestive or Oropharyngeal Decontaminationmentioning
confidence: 99%
“…A number of LL-37 related peptides have also shown the potential for therapeutic development [243,251], such as OP-145, which was developed by OctoPlus, and when the peptide was included in cream formulations for nasal application, these preparations were found to be efficacious in the eradication of MRSA carriage [252]. The anterior nares are the main reservoir for colonization by S. aureus and the nasal carriage of MRSA is an important risk factor for subsequent infection and transmission of this pathogen, which has led to intensive efforts to identify agents able to efficiently reduce MRSA colonization [253]. The completion of phase I/II clinical trials by OP-145 also showed that the peptide was safe and efficacious as a treatment for chronic otitis media, or chronic bacterial middle-ear infection (Table 2) [254].…”
Section: Potential Applications Of Ph Dependent Antimicrobial Peptmentioning
confidence: 99%